Integrative and Conjugative Elements (ICEs) in Pasteurellaceae Species and Their Detection by Multiplex PCR - Beker, Michal; Rose, Simon; Lykkebo, Claus A.; Douthwaite, Stephen (Frontiers in Microbiology, 2018)
Strains of the Pasteurellaceae bacteria Pasteurella multocida and Mannheimia haemolytica are major etiological agents of bovine respiratory disease (BRD). Treatment of BRD with antimicrobials is becoming more challenging due to the increasing occurrence of resistance in infecting strains. In Pasteurellaceae strains exhibiting resistance to multiple antimicrobials including aminoglycosides, beta-lactams, macrolides and sulfonamides, the resistance determinants are often chromosomally encoded within integrative and conjugative elements (ICEs). To gain a more comprehensive picture of ICE structures, we sequenced the genomes of six strains of P. multocida and four strains of M. haemolytica; all strains were independent isolates and eight of them were multiple-resistant. ICE sequences varied in size from 49 to 79 kb, and were comprised of an array of conserved genes within a core region and varieties of resistance genes within accessory regions. These latter regions mainly account for the variation in the overall ICE sizes. From the sequence data, we developed a multiplex PCR assay targeting four conserved core genes required for integration and maintenance of ICE structures. Application of this assay on seventy-five isolates of P. multocida and M. haemolytica reveals how the presence and structures of ICEs are related to their antibiotic resistance phenotypes. The assay is also applicable to other members of the Pasteurellaceae family including Histophilus somni and indicates how clustering and dissemination of the resistance genes came about.